Evektivitas Layanan Konseling Kelompok Pendekatan Behavioral melalui Teknik Shaping untuk Menurunkan Prokartinasi Akademik Mahasiswa Pascasarjana dalam Pembelajaran Daring - Nurul Ahwat Rantekata; Muh. Azhar Mubarak (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effectiveness of group counseling services using a behavioral approach through the shaping technique in reducing academic procrastination among postgraduate students at UIN Sunan Kalijaga during online learning. The participants consisted of 22 master’s students from the Interdisciplinary Islamic Studies program, with concentrations in Islamic Guidance and Counseling, Middle Eastern Studies, Library Science, and Islamic Educational Psychology, all of whom demonstrated high levels of procrastination based on questionnaire results. The research employed a quasi-experimental design with a one-group pretest-posttest model. Data were collected using a procrastination scale adapted from the study by Simamora and Letara. The data were analyzed using a non-parametric Paired Sample t-test. The results showed a Sig. (2-tailed) value of 0.000 < 0.05, indicating that group counseling services with a behavioral approach through the shaping technique effectively reduced procrastination among postgraduate students. These findings suggest that through gradual behavioral formation (shaping), students can develop study discipline, enhance academic responsibility, and reduce their tendency to delay academic tasks during online learning. Therefore, behavioral-based group counseling services significantly contribute to improving learning effectiveness among postgraduate students.